Acetylacetonato cobalt(III) and iron(III) complexes of picolylamine- and aminopropylamine-bis(phenolate) ligands: Synthesis, characterization and crystal structures. (15th January 2019) - Redjel, Yasmine K.; Thevenin, Lucas; Daran, Jean-Claude; Benslimane, Meriem; Poli, Rinaldo; Fliedel, Christophe
Graphical abstract: A series of acetylacetonato cobalt(III) and iron(III) complexes of tetradentate diamine-bis(phenolate) ligands was synthesized and fully characterized, including by X-ray crystallography. These complexes are thermally stable, even in the presence of vinyl monomers. Abstract: The reaction between [M(acac)3 ] (M = Fe, Co, acac = acetylacetonate) and the diamino-bis(phenol) pro-ligands (2-OH-3, 5- t Bu2 -C6 H2 CH2 )2 NCH2 (2-NC5 H4 ) (H2 1 ) and (2-OH-5- t Bu-C6 H3 CH2 )2 NCH2 CH2 CH2 N(CH3 )2 (H2 2 ) afforded the [κ 4 -( N 2, O 2 )M(acac)] complexes [Fe(1 )(acac)] (3 ), [Fe(2 )(acac)] (4 ), [Co(1 )(acac)] (5 ) and [Co(2 )(acac)] (6 ) in moderate yields after crystallization. The proposed formulas were supported by various analytical data (ESI-MS, FT-IR, EA, NMR), and the molecular structure of all complexes was confirmed by X-ray diffraction studies. In each octahedral complex, the diamino-bis(phenolate) ligand (1 or2 ) acts as a tetradentate ligand and the coordination sphere is completed by one chelating κ 2 - O 2 acac ligand. Although the previously reported ligand1 and the new ligand2 are very similar, their coordination to the Fe III (acac) or Co III (acac) moieties varies by the arrangement of the donor atoms. While the O phenolate donor atoms of ligand1 were found cis to each other in the Fe III complex3, they are trans in the Co III complex5, and vice versa for ligand2 . Since each ligand, 1 and2, exhibits both configuration, this structural curiosity cannot be easily explained on the basis of steric factors, i.e . ortho -substituents or N, N ′-linker length.